2022
DOI: 10.3390/nu14173615
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet and Atrial Fibrillation: Lessons Learned from the AFHRI Case–Control Study

Abstract: A relationship between lifestyle, diet, and atrial fibrillation (AF) remains unclear. Except for alcohol consumption, AF guidelines do not differentiate specific advice for this rhythm disorder. The aim of this study was to investigate the association between adherence to healthy dietary patterns and the presence of AF, among 104 low risk participants from the 1:1 matched case–control AFHRI (Atrial Fibrillation in High-Risk Individuals) study. Dietary data were obtained using a three-day food record. Adapted G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…36 In line with this, German studies reported a median MEDAS as low as three points. 20 We -D) and functional status (FFbH) by bootstrapping according to Lindemann, Merenda and Gold (1980, p.119ff, Relaimpo-Package R). For instance, the association of the PCS to the three components of a healthy lifestyle is estimated to be equally attributable to non-smoking, healthy diet and activity (around 30%), while activity is mainly responsible for the association of the functional status to a healthy lifestyle (around 60%) therefore chose the cut-off for the MEDAS in the current study to delineate a healthy lifestyle at four or higher.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…36 In line with this, German studies reported a median MEDAS as low as three points. 20 We -D) and functional status (FFbH) by bootstrapping according to Lindemann, Merenda and Gold (1980, p.119ff, Relaimpo-Package R). For instance, the association of the PCS to the three components of a healthy lifestyle is estimated to be equally attributable to non-smoking, healthy diet and activity (around 30%), while activity is mainly responsible for the association of the functional status to a healthy lifestyle (around 60%) therefore chose the cut-off for the MEDAS in the current study to delineate a healthy lifestyle at four or higher.…”
Section: Discussionmentioning
confidence: 99%
“…19 Patients may also benefit from other dietary patterns such as a traditional Asian diet, 19 gluten-free and vegan diet or fasting. 2 We did not account for these alternative potentially healthy dietary patterns, because previous studies in SLE mainly focused on a healthy Mediterranean diet, 2 we considered the latter pattern to likely be the most common amongst the healthy dietary patterns in Germany, 20,32 and due to practicality issues. As all patients in the study were Caucasian and German residents, we assumed alternative diets to be substantially less common in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, antibodies against heat shock protein 60 (HSP-60) expressed by periodontal pathogens can cross-react with hSP-60 in the host body to activate T cells, leading to endothelial damage and atherosclerotic plaque formation and mediating cardiovascular disease. However, whether MMPs or HSP-60-related immune responses of periodontal pathogens play important roles in atrial fibrillation remains unclear [27][28][29] .…”
Section: Conjecture About Related Underlying Mechanismsmentioning
confidence: 99%